The Effects of ROA, ROI, and Company Size on Audit Delay among IDX Companies Sanctioned for Late 2025 Interim Reporting - Septian Ade Saputra; Syakieb Arsalan (Golden Ratio of Auditing Research, 2027)
This research employs a descriptive, quantitative approach, drawing on secondary data from audited financial statements and annual reports. The research sample was selected using a purposive sampling method, comprising 24 companies and 120 observations. Return on Assets (ROA) was measured by dividing the net income by total assets; Return on Investment (ROI) was measured by by dividing the net income by the total cost of investment; and company size was measured using the natural logarithm of total assets. Audit delay was measured as the number of days between the end of the fiscal year and the date of the independent auditor's report. The results indicate that the Return on Assets (ROA) had a negative and significant effect on audit delay, Return on Investment (ROI) had no significant effect on audit delay, while company size had no effect on audit delay. These findings indicate that Return on Assets (ROA), play a greater role in determining audit timeliness than Return on Investment (ROI) and company size. This research is expected to provide practical implications for management and auditors in improving the efficiency and timeliness of audit completion.